Charlotte Luca’s Socio-Economic Choice in the Novel Pride and Prejudice: A Marxist-Feminist Perspective - Yakumbu, Stephanie; Ahmadi, Anas (International Journal of Language and Literature, 2025)
This study examines Charlotte Lucas’ marriage in Pride and Prejudice through a Marxist-feminist lens. Elizabeth Bennet’s romantic autonomy is often celebrated. This study highlights Charlotte’s pragmatic marriage as a strategic response to the constraints of class and gender that interact with each other. This study aims to examine Charlotte Lucas's socio-economic choices in Pride and Prejudice from a Marxist-Feminist perspective, highlighting the relationship between social class, economy, and gender in marriage decision-making. Through a thematic reading supported by Fraser’s three-dimensional theory of economic, cultural, and political justice and Walby’s intersectional theory of systems of oppression, this study argues that Charlotte’s choices reflect constrained agency shaped by structural constraints rather than passive obedience. Austen’s narrative is interpreted as a critique of the capitalist-patriarchal order that governs women’s lives by positioning Charlotte not as a submissive individual but as a figure navigating the struggle to survive within an oppressive social framework. In conclusion, Charlotte Lucas’ socio-economic choices in the novel Pride and Prejudice reflect the condition of women who are structurally marginalized in a patriarchal and capitalist society, where marriage is the only safe path to survival. The implication is that Charlotte Lucas’ socio-economic choices reflect the reality of middle-class women constrained by patriarchal systems and economic pressures in 19th-century English society. Through a Marxist-Feminist perspective, this study highlights how marriage becomes a survival strategy driven by class inequality and women’s economic dependence on men.